TYPHA CAPENSIS EXTRACTS DECREASE ROS PRODUCTION AND AFFECT HUMAN SPERM FUNCTIONS - Henkel, R.; Fransman, W.; Hipler, U.; Schreiber, G. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
South African traditional healers use about 3,000 higher plants to treat ailments and diseases. As about 25% of prescribed medicines contain plant extracts, an immense need exists to test the effects of these plants and their compounds on male reproductive functions. The objective of this study was to investigate the in vitro effects of extracts from Typha capensis on sperm motility, viability, production of reactive oxygen species (ROS) and the mitochondrial membrane potential (MMP). Fifty semen samples were washed with Human Tubular Fluid Medium containing 10 mg/ml albumin and a swim-up was performed. To 100 Âµl swim-up fraction, 1 Âµg/ml freeze-dried aqueous extract of Typha rhizome was added and incubated for 1 hour at 37Â°C. Parameters were analyzed in the test samples, controls as well as in the pellet. Sperm viability was assessed by means of the Eosin stain. Sperm ROS production was tested by means of dihydroethidine and MMP using the DePsipher kit. To inhibit superoxide production by the extract at different concentrations (0.1 mg/ml; 0.05 mg/ml and 0.01 mg/ml) the Antioxidant Kit with PholasinÂ® was used. Statistical analysis was performed using the MedCalc software ver. 9.4.2. Results: Results showed significantly (P<0.0001) decreased motility (81.4% vs. 95.3%), viability (70.8% vs. 77.6%), MMP (49.0% vs. 67.5%) and sperm ROS production (11.3% vs. 14.9%) after incubation with Typha extract. The inhibition of ROS production was significantly dose-dependent. Results also indicated a decreased MMP (P<0.0001) and viability (P<0.0001) in the pellet when compared to the swim-up. Conclusions: Typha capensis extracts had significant detrimental effects on various sperm functions in vitro. It also decreased the cells’ ROS production, which could have a negative effect on cellular functions. Moreover, centrifugation not only affects sperm motility and viability but also mitochondrial functionality.